Schild Analysis of the Interaction between Parthenolide and Cocaine Suggests an Allosteric Relationship for Their Effects on Planarian Motility - Jyothi Kakuturu; Mary O’Brien; Oné R. Pagán (Biomolecules)
The freshwater planarian is an emerging animal model in neuroscience due to its centralized nervous system that closely parallels closely parallels the nervous system of vertebrates. Cocaine, an abused drug, is the ‘founding member’ of the local anesthetic family. Parthenolide, a sesquiterpene lactone, acts as a behavioral and physiological antagonist of cocaine in planarians and rats, respectively. Previous work from our laboratory showed that both parthenolide and cocaine reduced planarian motility and that parthenolide reversed the cocaine-induced motility decrease at concentrations where parthenolide does not affect the movement of the worms. However, the exact mechanism of the cocaine/parthenolide antagonism is unknown. Here, we report the results of a Schild analysis to explore the parthenolide/cocaine relationship in the planarian Girardia tigrina. The Schild slopes of a family of concentration–response curves of parthenolide ± a single concentration of cocaine and vice versa were −0.55 and −0.36, respectively. These slopes were not statistically different from each other. Interestingly, the slope corresponding to the parthenolide ± cocaine (but not the cocaine ± parthenolide) data set was statistically different from −1. Our data suggest an allosteric relationship between cocaine and parthenolide for their effect on planarian motility. To the best of our knowledge, this is the first study about the mechanism of action of the antagonism between cocaine and parthenolide. Further studies are needed to determine the specific nature of the parthenolide/cocaine target(s) in this organism.